Probabilistic safety assessment method for spent nuclear fuel road transportation. (March 2020) - Tao, Longlong; Wang, Jin; Long, Pengcheng; Wang, Dagui; Wang, Fang; Zhou, Baichang; Chen, Jun
Highlights: The PSA method for spent nuclear fuel road transportation is proposed. The PVCRES risk indicators are proposed and quantified to characterize the risks. An ET/FT integrated model is constructed in order to assess the process risks. The risk level is quantified and targeted improvement approaches are proposed. Abstract: Spent Nuclear Fuel (SNF) transportation has the potential possibility of releasing radioactivity, thus it is significant to assess the transportation risks and take effective measures to improve its safety. Current researches were mainly focused on the assessment of the transportation consequences, which lacked detailed and systematic analysis of the transportation process. In this paper, Probabilistic Safety Assessment (PSA) method for SNF Road Transportation (SNFRT) is proposed. The PVCRES (personnel, vehicle, cask, road, environment, supervision and management) risk indicators are proposed and quantified to characterize the risks that exist during the transportation process, which is in line with the actual situation. Then an ET/FT integrated model is established in order to assess the risk of SNFRT process from a certain Nuclear Power Plant (NPP) to the reprocessing plant. The risk level is quantified and targeted improvement approaches are proposed to demonstrate the feasibility and effectiveness of this method.